Ten Steps to Conducting a Large, Multi-Site, Longitudinal Investigation of Language and Reading in Young Children - , Language; Reading Research Consortium (LAARC); Farquharson, Kelly; Murphy, Kimberly A. (Frontiers in Psychology, 2016)
Purpose: This paper describes methodological procedures involving execution of a large-scale, multi-site longitudinal study of language and reading comprehension in young children. Researchers in the Language and Reading Research Consortium (LARRC) developed and implemented these procedures to ensure data integrity across multiple sites, schools, and grades. Specifically, major features of our approach, as well as lessons learned, are summarized in ten steps essential for successful completion of a large-scale longitudinal investigation in early grades. Method: Over five years, children in preschool through third grade were administered a battery of 35 higher- and lower-level language, listening, and reading comprehension measures. Data were collected from children, their teachers, and their parents/guardians at four sites across the United States. Substantial and rigorous effort was aimed toward maintaining consistency in processes and data management across sites for children, assessors, and staff. Conclusion: With appropriate planning, flexibility, and communication strategies in place, LARRC developed and executed a successful multi-site longitudinal research study that will meet its goal of investigating the contribution and role of language skills in the development of children’s listening and reading comprehension. Through dissemination of our design strategies and lessons learned, research teams embarking on similar endeavors can be better equipped to anticipate the challenges.